2021
DOI: 10.1371/journal.pone.0253474
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP24A1 gene polymorphism with colorectal cancer in the Jiamusi population

Abstract: Background The population in Jiamusi has been reported to have the highest prevalence of colorectal cancer (CRC) in China. The genetic causal-effect for this occurrence among the residents remains unclear. Given the long cold seasons with people wearing more clothes and reduced UV exposure, we aimed to study the association between the vitamin D metabolism-related gene CYP24A1 polymorphism and CRC susceptibility. Method A case-control study was conducted that included 168 patients with CRC and 710 age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Studies have shown that the occurrence and development of most colorectal cancer is related to environmental factors, such as dietary intake and the surrounding environment 1 , 2 . Epidemiological survey has indicated that cold exposure may not only be closely associated with high incidence of colorectal cancer, but also with malignant metastasis 3 . In addition, chili-pepper was positively associated with colorectal cancer incidence 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the occurrence and development of most colorectal cancer is related to environmental factors, such as dietary intake and the surrounding environment 1 , 2 . Epidemiological survey has indicated that cold exposure may not only be closely associated with high incidence of colorectal cancer, but also with malignant metastasis 3 . In addition, chili-pepper was positively associated with colorectal cancer incidence 4 .…”
Section: Introductionmentioning
confidence: 99%
“…11 The CYP24A1 rs4809957 polymorphism AA genotype significantly increased the risk of CRC 2.38 (1.30-4.37) times (p = 0.005). Research by Chai et al (2021) shows that CYP24A1 polymorphisms are more common in low-grade CRC patients (p = 0.15). 24 Sun et al (2016) also found a similar study, which showed that CYP24A1 polymorphisms were more common in low-grade CRC patients with insignificant results (p = 0.137).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Chai et al (2021) shows that CYP24A1 polymorphisms are more common in low-grade CRC patients (p = 0.15). 24 Sun et al (2016) also found a similar study, which showed that CYP24A1 polymorphisms were more common in low-grade CRC patients with insignificant results (p = 0.137). 11 Meanwhile, another study by Gong et al (2017) in China with 528 samples showed that the CYP24A1 rs4809957 A/G polymorphism had a statistically significant association with the risk of colon polyps, colon cancer and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations